RISK ANALYSIS OF PESTE DES PETITS RUMINANTS INTRODUCTION INTO THE TERRITORY OF THE RUSSIAN FEDERATION - S. V. Scherbinin; A. K. Karaulov; V. M. Zakharov (Ветеринария сегодня)
Peste des petits ruminants (PPR) has never been registered in the Russian Federation, but the epidemic situation in the neighboring countries indicates that it is a typical transboundary disease. Due to significant social and economic losses, negative effect on food safety of many countries of the world, peste des petits ruminants has been included in the List of priority diseases of the FAO/OIE Global Framework for the Progressive Control of Transboundary Animal Diseases (GF-TADs) A Five-Year Action Plan. The disease has already spread in the countries which share borders with Russia, therefore there is an urgent need to assess the risk of introduction and subsequent spread of peste des petits ruminants in the territory of the Russian Federation. The performed analysis of PPR epidemic situation and disease spread tendencies in the Russian Federation neighboring countries over the last years using map documents and government sources has demonstrated that there is a high risk of PPR penetration into the territory of our country. The epidemic situation in Mongolia and China, in Georgia, Turkey and Iran is of primary concern.